2021
DOI: 10.1007/s11030-021-10239-x
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models for classification tasks related to drug safety

Abstract: In this review, we outline the current trends in the field of machine learning-driven classification studies related to ADME (absorption, distribution, metabolism and excretion) and toxicity endpoints from the past six years (2015–2021). The study focuses only on classification models with large datasets (i.e. more than a thousand compounds). A comprehensive literature search and meta-analysis was carried out for nine different targets: hERG-mediated cardiotoxicity, blood–brain barrier penetration, permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 119 publications
1
18
0
Order By: Relevance
“…Based on the six case studies, we can support our previous analysis of the ADME-Tox-related classification models ( Rácz et al, 2021 ). Here, we have found that the XGBoost algorithm could outperform the neural network-based models, which is consistent with the findings in the mentioned publication: the tree-based algorithms have high priority over the others in the ADME-Tox-related models from the literature of the last 5 years.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Based on the six case studies, we can support our previous analysis of the ADME-Tox-related classification models ( Rácz et al, 2021 ). Here, we have found that the XGBoost algorithm could outperform the neural network-based models, which is consistent with the findings in the mentioned publication: the tree-based algorithms have high priority over the others in the ADME-Tox-related models from the literature of the last 5 years.…”
Section: Discussionsupporting
confidence: 74%
“…The best benchmark models cannot be determined based on solely one criterion. According to the literature data in our review ( Rácz et al, 2021 ), the present models fit into the average performance in each case study. Moreover, Figure 10C shows that the best of the developed models sometimes can be even better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physicochemical, pharmacokinetic, and toxicity parameters of the compounds ( Table 2 ) are as follows: the logarithm of the partition coefficient (log P ) in the n -octanol/water system, the number of hydrogen bond donors ( HBD ), acceptors ( HBA ), and rotatable bonds ( NRB ), molar weight ( MW ), topological polar surface area ( TPSA ) [ 24 ], the volume of distribution in the body ( V d ) [ 25 ], the fraction unbonded in a brain ( f u, brain ), in plasma ( f u, plasma ) [ 26 ], and pharmacokinetic parameters describing blood–brain distribution (log BB ) [ 26 , 27 , 28 , 29 ], the rate of permeation from aqueous solutions through skin (log K p ) [ 30 , 31 ], skin–water partition coefficient (log K sc ) describing dermal absorption from aqueous solutions [ 32 , 33 ], the rate of permeation through cell (log K w/cell ) [ 34 ], partitioning between water and serum albumin (log P w/HSA ), and binding to human serum albumin (log K HSA ) [ 10 , 35 , 36 , 37 ], partitioning between water and plant’ cuticles (log P w/pc ) [ 38 ], and the dose causing the death of 50% of the group of mice tested after oral administration ( LD 50 ) [ 39 , 40 ]. These parameters describe important properties of the test substances and provide information about their potential applications as pesticides as well as potential threats to humans [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%